Las relaciones entre la Unión Europea y Rusia - Cámara Hermoso, Manuel De La (UNISCI Discussion Papers, 2008)
The relationship between the EU and Russia is of fundamental importance, but enormously complex and difficult. It is necessary that the EU develops a feasible policy towards Russia, but also ambitious. Relations with Russia, which in fact are in a deadlock, are too important to be hindered by any bilateral problem. The EU must treat Russia as what it is: a very important strategic partner, and try to involve it step by step in the system of rules and values that the European project represents.